Individual and Environmental Impacts on Sexual Health of Caribbean youth - Sarah J. Lerand; Marjorie Ireland; Robert W. Blum (The Scientific World Journal)
Individual health risk behaviors among Caribbean youth account for the majority of adolescent morbidity and mortality in that area. This study explores the associations between individual factors, socioenvironmental factors, and sexual healthrelated behaviors in Caribbean youth. Data from the 1995 Caribbean Youth Health Survey, a nine-country, cross-sectional study completed by 15,695 in-school youth 10—18 years of age were analyzed. One-third of the sample (n = 5,060) reporting sexual activity was analyzed. This study examined age at first sexual intercourse, number of sexual partners, history of pregnancy, and condom use. The predictor variables were rage, depressed mood, expectation of early death, self-reported school performance, parental mental health or substance abuse problems, and family connectedness. Bi- and multivariate analyses were done separately for males and females, controlling for age, to examine associations between individual and socioenvironmental factors and sexual health behaviors. In the multivariate model, there were associations between rage, abuse, family mental health and substance use, anticipation of early death, and many of the outcome variables in males and females. Family connectedness and positive self-reported school status were correlated with greater condom use at last intercourse in males. Family connectedness was correlated with older age at first sexual intercourse. Depressed mood was not correlated with any of the outcome variables.The findings of the study demonstrate an association between individual and socioenvironmental factors and sexual health behaviors in the lives of Caribbean youth. Strong associations between rage and physical/sexual abuse and risky sexual behaviors are of notable concern.